Tinjauan Pasal 33 UUD 1945 terhadap Praktik Kontrak Karya di Indonesia - Fuad Ahsan; Lukman Santoso (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2017)
Indonesia is a country rich in natural resources. In the management of natural resources has been regulated in Article 33 of the Basic Law (UUD/Constitution) of 1945, which mandated to prioritize the welfare of the people in its management. This article aims to study the problems of implementation of the contract of work in Indonesia in the review of Article 33 UUD 1945 which is the foundation in the natural resource management in Indonesia. In the practice of contract of work in Indonesia there are many other problems arising from the implementation of the contract of work in Indonesia. This is because the policy and implementation of the work contract that has not been in accordance with the provisions contained in Article 33 of the Constitution, 1945. Additionally, realize the mandate of Article 33 of the 1945 Constitution are extremely vital and urgent. This is in order to create a uniform public welfare in a sustainable manner and not create unequal economic growth and controlled by the investor or foreign.